1998
DOI: 10.1046/j.1529-8817.1998.340655.x
|View full text |Cite
|
Sign up to set email alerts
|

Rubisco Adaptation to Low Temperatures: A Comparative Study in Psychrophilic and Mesophilic Unicellular Algae

Abstract: Some properties of the ribulose‐1,5‐bisphosphate carboxylase/oxygenase (RUBISCO) from two psychrophilic Chloromonas species have been investigated in relation to their adaptation to cold environments. Contrary to the situation usually encountered with psychrophilic enzymes, the carboxylase activity of both purified “cold” RUBISCO enzymes was lower at low temperatures than that found with the enzyme of the mesophilic alga Chlamydomonas reinhardtii Dangeard. Moreover, the apparent optimal temperature for RUBISCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 24 publications
6
42
1
Order By: Relevance
“…A similar trend was observed in winter-hardened-crops species (232). Conversely, the protein was thermally sensitive to inactivation in both Antarctic algae and plants (42,236). While sequence analysis and modeling of the large subunit (rbsL) of Rubisco in the psychrophilic Chloromonas sp.…”
Section: Cold-adapted Enzymessupporting
confidence: 61%
See 1 more Smart Citation
“…A similar trend was observed in winter-hardened-crops species (232). Conversely, the protein was thermally sensitive to inactivation in both Antarctic algae and plants (42,236). While sequence analysis and modeling of the large subunit (rbsL) of Rubisco in the psychrophilic Chloromonas sp.…”
Section: Cold-adapted Enzymessupporting
confidence: 61%
“…In contrast with argininosuccinate lyase, the temperature maximum for carboxylase activity of ribulose-1,5-bisphosphate carboxylase (Rubisco), one of the most critical enzymes for inorganic carbon fixation in phototrophs, was not altered in two isolates of the Antarctic Chloromonas sp., and the specific activity at low temperatures was actually lower in the psychrophilic compared with the mesophilic Rubisco (42). This was one of the few exceptions described so far of a psychrophilic enzyme not exhibiting higher catalytic activity at lower temperatures.…”
Section: Cold-adapted Enzymesmentioning
confidence: 71%
“…The optimum temperature in the Antarctic species was 208C lower. However, Devos et al (1998) found that the CO 2 -fixing enzyme Rubisco was not more cold stable than in C. reinhardtii, but the relative amount of the enzyme was twice as high. This was discussed as a novel adaptation strategy.…”
Section: Discussionmentioning
confidence: 89%
“…This behaviour is defined by the temperature coefficient Q 10 , which describes a rate change per change of 10 • C in temperature. An average value of 2-3 for the Q 10 of the carboxylating enzyme ribulose-1,5-bisphosphate carboxylase/oxygenase (RubisCO) has been measured in phytoplankton in general and recently verified for SO species (Descolas-Gros and de Billy, 1987; Devos et al, 1998;Sage, 2002;Young et al, 2015). Using this coefficient, if SST of the SO were to rise by 6 • C, it would result in an approximate doubling of physiological activity (growth).…”
Section: Temperaturementioning
confidence: 97%